Synchronous primary cancers of trachea and esophagus and ventricular tachycardia - Luo, Wen; Luo, Guomin; Gong, Youling; Wang, Jin (Chinese Journal of Cancer Research; Vol 26, No 3 (June 01, 2014): Chinese Journal of Cancer Research, 2014)
The incidence of multiple primary cancers involving trachea is rare. We present a case of synchronous double primary cancer of trachea and esophagus in a 70-year-old woman, with a special symptom of ventricular tachycardia and no history of smoking and alcohol drinking. Biopsies from multiple foci demonstrated the patient had primary small cell cancer of trachea and squamous cell carcinoma in situ of esophagus. The patient was successfully treated with four cycles of chemotherapy consisting of etoposide and carboplatin (EC) followed by thoracic radiotherapy (60 Gy in 30 fractions, in 6 weeks), and was evaluated to have complete response of tumor. To our knowledge, there is no synchronous cancer of trachea and esophagus has been reported in English literature, and our experience showed sequential EC chemotherapy and radiotherapy provided an effective treatment to control both cancers.